2021
DOI: 10.1001/jamanetworkopen.2021.1320
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Trauma Admissions During the COVID-19 Pandemic in Los Angeles County, California

Abstract: IMPORTANCEDescribing the changes in trauma volume and injury patterns during the course of the coronavirus disease 2019 (COVID-19) pandemic could help to inform policy development and hospital resource planning. OBJECTIVE To examine trends in trauma admissions throughout Los Angeles County (LAC) during the pandemic. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study, all trauma admissions to the 15 verified level 1 and level 2 trauma centers in LAC from January 1 to June 7, 2020 were reviewed. All trauma ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
101
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 19 publications
14
101
1
3
Order By: Relevance
“…Many other studies regarding trauma have found similar increases in penetrating trauma. Southern California 24 penetrating trauma increased from 10.3% to 13.0%, A Los Angeles County study 20 separately identified increase in penetrating trauma 15.4% to 15.7%, Philadelphia 19 penetrating trauma increased 17.5% to 23.7%, and San Francisco 16 violence related injuries increased 17% to 46%. This study identified a concurrent decrease in blunt trauma accompanying the increased proportions of penetrating trauma which is similar to previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many other studies regarding trauma have found similar increases in penetrating trauma. Southern California 24 penetrating trauma increased from 10.3% to 13.0%, A Los Angeles County study 20 separately identified increase in penetrating trauma 15.4% to 15.7%, Philadelphia 19 penetrating trauma increased 17.5% to 23.7%, and San Francisco 16 violence related injuries increased 17% to 46%. This study identified a concurrent decrease in blunt trauma accompanying the increased proportions of penetrating trauma which is similar to previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…The difference in hospital LOS is relatively small and coincides with no difference in ICU LOS found in previous reports. 20 While mortality differences fluctuated throughout the year, the greatest mortality among trauma patients in 2020 occurred in March (3.06%) and April (3.11%), then again in November (3.10%) and December (3.56%). The peaks in mortality occur during the initial stay-at-home orders and the third peak of COVID-19 positivity yet the explanation for this change in mortality is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrary to our results, Yeates et al found a shorter length of stay in the post-stay-at-home order group [ 15 ]. Ghafil and colleagues reported no differences in mean HLOS between the groups [ 7 ]. And Devarakonda et al, like our findings, stated that mean HLOS increased in the COVID-19 period [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the leading reasons for emergency admissions is traumatic injuries. In the literature, many studies reported that there was also a decrease in admissions to the emergency departments attributable to trauma during the COVID-19 pandemic [6][7][8][9]. The vast majority of these studies were associated with orthopedic injuries and did not contain abdominal trauma patients.…”
Section: Introductionmentioning
confidence: 99%